The Darling Dahlias and the silver dollar bush [large type] - Albert, Susan Wittig (Albert, Susan Wittig. Darling Dahlias mysteries, 2014)
It's the spring of 1933 and times are tough all over. Banks are closing all over the country, and the small town of Darling, Alabama, is no exception. Desperate to avoid disaster, several town leaders hatch a plan to print Darling Dollars on the newspaper printing press to serve as temporary currency so the town can function. But when the first printing of the scrip disappears, the Darling Dahlias set out to discover who made an unauthorized withdrawal.